2009
DOI: 10.1016/j.cellbi.2009.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells showed the highest potential for the regeneration of injured liver tissue compared with other subpopulations of the bone marrow

Abstract: We have previously reported that bone marrow cells (BMCs) participate in the regeneration after liver injury. However, it is not established that this is the result of differentiation of hematopoietic stem cells (HSCs), mesenchymal stem cells (MSCs) or the combination of both. We investigated the contribution of each cell fraction to the regenerative process. First, we confirmed that transplanted stem cells migrate directly to injured liver tissue without dispersing to other organs. Next, we divided green fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 18 publications
5
72
0
2
Order By: Relevance
“…BMSC therapy currently represents a promising strategy for ALF treatment (Sato et al, 2005;Cho et al, 2009). The present study demonstrated that BMSC transplantation attenuates liver damage by reducing the infiltration of inflammatory cells and inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BMSC therapy currently represents a promising strategy for ALF treatment (Sato et al, 2005;Cho et al, 2009). The present study demonstrated that BMSC transplantation attenuates liver damage by reducing the infiltration of inflammatory cells and inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell suspensions were incubated with different antibodies, including FITC-labeled anti-rat CD45, CD29, CD11, and CD90 (Sato et al, 2005;Cho et al, 2009) (all from BioLegend, USA), at a recommended dilution (1:100) for 30 min at room temperature in the dark. Isotype-identical antibodies (IgG) served as controls.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Son multipotenciales, diferencián-dose hacia adipocitos, osteoblastos, condrocitos, tenocitos, miocitos, estroma hematopoyético y fibroblastos 6 . Presentan plasticidad para diferenciarse ex-vivo a tejidos no mesodermales, como neuronas, astrocitos, oligodendrocitos, neumocitos y hepatocitos 7,8 . La Sociedad Internacional de Terapia Celular (ISCT) ha sugerido criterios mínimos para definir una MSC: a) adherencia al plástico bajo condiciones estándar de cultivo; b) expresión de marcadores de superficie como CD105, CD90, CD73 y ausencia de marcadores, sobre todo hematopoyéticos, incluyendo CD45, CD34, CD14 y CD11b; c) capacidad de diferenciación in-vitro hacia los otros linajes de origen mesodermal (adipocitos, condrocitos, osteoblastos) 9 .…”
Section: Características Generalesunclassified
“…Biological signals released from the injured area and corresponding receptors expressed on the cell surface of MSCs are critical determinants of this step (16).…”
Section: Mechanism Of Bm Cells Homing To the Livermentioning
confidence: 99%